Study on prescribing patterns of parenteral antibiotics in medical and surgical units of Hospital Batu Pahat - Sairan, Mohd Roslezam; Abdul Rahman, Amril Nurman; Nordian@Nordin, Mohd Faizalhafiz; Ahmad, Mohd Azamudin (2009)
Objective: To determine the prescribing patterns of parenteral antibiotics in the medical and surgical units of Hospital Batu Pahat including the single agent and combination agent used most frequently for the treatment, the most commonly used agent, the most common infection treated and the antibiotics used, and the total cost spent on parenteral antibiotics.